2012
DOI: 10.2174/1874357901206010068
|View full text |Cite
|
Sign up to set email alerts
|

The E89K Mutation in the Matrix Protein of the Measles Virus Affects In Vitro Cell Death and Virus Replication Efficiency in Human PBMC

Abstract: Matrix protein is known to have an important role in the process of virus assembly and virion release during measles virus replication. In the present in vitro study, a single mutation of E89K in the matrix protein was shown to affect cell death and virus replication efficiency in human PBMC. One strain with this mutation caused less cell death than the parental virus, and possessed high virus replication efficiency. Moreover, by Annexin V-FITC staining, polycaspase FLICA staining, and double labeling with pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The aa substitutions in the M protein, namely E89K (PMV-2990) and R175G (DMV-muc), have also been shown to be important in MV cell culture adaptation 30 , 31 . In particular, experiments with the E89K substitution in MV have demonstrated that this mutation can facilitate virus infection in Vero cells and cotton rats 31 , 47 . Interestingly, some morbillivirus vaccine strains also contain these changes at positions 5 and 12 of the leader sequence, which we identified in this study (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The aa substitutions in the M protein, namely E89K (PMV-2990) and R175G (DMV-muc), have also been shown to be important in MV cell culture adaptation 30 , 31 . In particular, experiments with the E89K substitution in MV have demonstrated that this mutation can facilitate virus infection in Vero cells and cotton rats 31 , 47 . Interestingly, some morbillivirus vaccine strains also contain these changes at positions 5 and 12 of the leader sequence, which we identified in this study (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1D). Note that we conducted a more thorough mutational analysis of the glutamic acid residue at position 89 (Table 1), given that this amino acid was reported to influence MeV replication both in vitro and in vivo (36)(37)(38)(39)(40). Overall, we intended in this study to generate M mutants exclusively deficient in triggering late stages of the viral life cycle (i.e., membrane budding) while preserving other functions mostly unaltered (i.e., folding, intracellular transport-competence, interaction with the nucleocapsid protein [N], and localization with the plasma membrane).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies revealed a role of the amino acid at position 89 of MeV-M as an important determinant for adaptation and growth of the virus in Vero cells (36,37). Indeed, while the substitutions E89G and E89K allowed the virus to adapt to Vero cells, the mutant M-E89K enabled MeV to more efficiently infect cotton rats and affect virus replication in human peripheral blood mononuclear cells (PBMCs) (37)(38)(39)(40). Finally, M-driven membrane budding may also rely on its capacity to associate with cellular membranes, as well as to self-assemble into stable dimers, which in turn may form proper building blocks to assemble high-order oligomers (6,14,19,21,22).…”
mentioning
confidence: 99%